Social innovation as a collaborative concept - Ziegler, Rafael (Innovation: The European Journal of Social Science Research, 2017)
The rise of social innovation expresses a discontent with innovation as we know it, and its ability to deliver just and sustainable outcomes. Yet, social innovation is also notoriously vague as a concept, thereby putting into doubt whether the concept offers any real improvements or alternatives. This paper issues an invitation to think about social innovation as a collaborative concept. The conceptual framework shows collaboration, rather than contestation, to offer a space for the working together of different perspectives and actors. The collaborative concept frame welcomes and seeks to explain a diversity of uses. Singling out key features of social innovation as a collaborative concept, it seeks to contribute to an emerging practice that makes different contributions part of a progressive conversation about social innovation, the evaluative ideas associated with it and the evidence from policies and projects. Identifying transformative, taxonomical and transitional–sceptical uses of social innovation, the paper highlights the importance of analysing the evaluative aspects of the multisectoral reconfigurations associated with social innovation so as to keep track of its role for justice and sustainability.
Publisher: Routledge _eprint: https://doi.org/10.1080/13511610.2017.1348935
Keywords: Collaboration; Innovation sociale; Éthique

Co-création de valeur et technologie digitale : quel design pour ces plateformes d’engagement ? Le cas du Photomaton 2.0 - Abbes, Intissar; Troudy, Yossra (Management Avenir, 2017)
Cette recherche traite du rôle des plateformes technologiques pour engager le client dans un processus de co-création de valeur avec l’entreprise. Le cas du Photomaton digital (Sharingbox) est étudié. Des entretiens semi-directifs menés auprès de clients participants à trois événements de marques mais aussi auprès de managers et de responsables de l’entreprise Sharingbox révèlent le rôle de cette technologie à engager les participants dans un acte de co-création en ligne avec la marque, acte qui peut se révéler engageant dans le temps. Cependant, l’efficacité de ces plateformes d’engagement semble contingente aux valeurs perçues de l’expérience de la technologie, à l’image de la marque et au profil de ses clients.
Number: 4 Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: Management Prospective Ed.
Keywords: Co-création; Co-innovation; Co-promotion; Collaboration; Entreprise; Nouvelles technologies; Partenariat; Réservé UdeM

Le living lab, un intermédiaire d’innovation ouverte pour les territoires ruraux ou péri-urbains ? - Fasshauer, Ingrid; Zadra-Veil, Cathy (Innovations, 2020)
L’objectif de cet article est d’analyser une nouvelle forme organisationnelle, le living lab (LL) et sa capacité à favoriser l’innovation territoriale en milieu rural ou péri-urbain. A travers une revue de littérature et la mobilisation de la sociologie de l’acteur-réseau (Callon, 1986 ; Latour, 1987), nous positionnons les living labs comme intermédiaires d’innovation ouverte dont les caractéristiques permettent d’intégrer de nombreux acteurs hétérogènes, établissements publics, entreprises privées, associations et citoyens, sur des projets d’innovation. L’étude d’un LL rural met en évidence la capacité d’une telle structure à reconfigurer des réseaux d’acteurs pour proposer une série de tiers-lieux adaptés aux spécificités des territoires sur lesquels ils s’implantent. Cette recherche permet d’enrichir la réflexion la pérennisation des tiers-lieux ruraux et leurs spécificités par rapport aux espaces urbains.
Number: 1 Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: De Boeck Supérieur
Keywords: Collaboration; Innovation; Innovation ouverte; Laboratoire vivant; Living Labs; Réservé UdeM; Économie collaborative

Les enjeux de la transition numérique et de l’innovation collaborative dans les mutations du travail et du management dans le secteur public - Zacklad, Manuel (Travailler dans les services publics : la nouvelle donne, 2020)
La transformation numérique et l’innovation collaborative ou les notions associées « d’intelligence collective », de « design thinking », « d’agilité » sont en passe de devenir les principaux concepts à la mode du management dans les organisations privées et publiques, au moins au sein des sièges et des directions centrales. Partant d’une description des spécificités des bouleversements introduits par la transition numérique et des technologies capacitantes qu’elle promeut, nous montrons comment les opérateurs sont parfois en demande de plus d’innovations numériques pour améliorer leurs conditions de travail et les services rendus au public, pour autant que celles-ci ne soient pas substitutives et excessivement rationalisantes. Les démarches d’innovation collaborative, soutenues par le haut management de manière parfois paradoxale, contribuent à faciliter ces mutations.
Publication Title: Travailler dans les services publics : la nouvelle donne
Keywords: Co-design; Collaboration; Innovation agile; Innovation collaborative; Intelligence collective; Numérique; Réservé UdeM; Secteur public

Data activism and social change - Gutiérrez, Miren (Palgrave Macmillan, 2018)
This book efficiently contributes to our understanding of the interplay between data, technology and communicative practice on the one hand, and democratic participation on the other. It addresses the emergence of proactive data activism, a new sociotechnical phenomenon in the field of action that arises as a reaction to massive datafication, and makes affirmative use of data for advocacy and social change. By blending empirical observation and in-depth qualitative interviews, Gutiérrez brings to the fore a debate about the social uses of the data infrastructure and examines precisely how people employ it, in combination with other technologies, to collaborate and act for social change.
Keywords: Changement social; Collaboration; Data collaboratives; Réservé UdeM; Technologie

Contexts of Co-creation: Designing with System Stakeholders - Jones, Peter (Systemic Design: Theory, Methods, and Practice, 2018)
The concept of co-creation includes a wide range of participatory practices for design and decision making with stakeholders and users. Generally co-creation refers to a style of design or business practice characterized by facilitated participation in orchestrated multi-stakeholder engagements, such as structured workshops and self-organizing modes of engagement. Co-creation envelopes a wide range of skilled social practices that can considerably inform and enhance the effectiveness of organizational development, collaboration, and positive group outcomes. New modes of co-creation have emerged, evolving from legacy forms of engagement such as participatory design and charrettes and newer forms such as collaboratories, generative design, sprints, and labs. Often sessions are structured by methods that recommend common steps or stages, as in design thinking workshops, and some are explicitly undirected and open. While practices abound, we find almost no research theorizing the effectiveness of these models compared to conventional structures of facilitation. As co-creation approaches have become central to systemic design, service design, and participatory design practices, a practice theory from which models might be selected and modified would offer value to practitioners and the literature. The framework that follows was evolved from and assessed by a practice theory of dialogic design. It is intended to guide the development of principles-based guidelines for co-creation practice, which might methodologically bridge the wide epistemological variances that remain unacknowledged in stakeholder co-creation practice.
Keywords: Co-création; Collaboration; Japon; Recommandations; Réservé UdeM

University Medialabs: New Learning Spaces for Educational Innovation - Almaraz-Menéndez, Fernando; Martín-García, Teresa; López-Esteban, Carmen (Journal of Strategic Innovation and Sustainability, 2021)
Higher Education Institutions, like many other organizations, are facing pressure from the development of digital technologies as a push towards the digitization of their activities and towards a type of change that some describe as disruptive and that forces them to review their processes and structures. This article describes the case of the medialab of the University of Salamanca, MEDIALAB USAL, as an experience of new learning space in higher education. Its origin is explained from the experiences of citizen technology laboratories and experimental laboratories at the point of intersection between Art, Science and Technology. Its structure and working methods are explained, and its activities are illustrated through the description of four educational innovation projects based on different digital technologies: a mathematics didactics project using AppInventor, Wikipedia as a tool for knowledge generation, Arduino for innovation in the teaching of Fine Arts and a university Hackathon as an activity to introduce students to social and entrepreneurial innovation processes.
Number: 4
Keywords: Collaboration; Durabilité; Europe; Innovation pédagogique; Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Rôle des universités; Technologies; numérique

Using Social Innovation as a Theoretical Framework to Guide Future Thinking on Facilitating Collaboration Between Mental Health and Criminal Justice Services - Hean, Sarah; Willumsen, Elisabeth; Ødegård, Atle; Bjørkly, Stål (International Journal of Forensic Mental Health, 2015)
Offender mental health is a major societal challenge. Improved collaboration between mental health and criminal justice services is required to address this challenge. This article explores social innovation as a conceptual framework with which to view these collaborations and develop theoretically informed strategies to optimize interorganizational working. Two key innovation frameworks are applied to the offender mental health field and practice illustrations provided of where new innovations in collaboration, and specifically co-creation between the mental health system and criminal justice system, take place. The article recommends the development of a competency framework for leaders and front line staff in the mental health system and criminal justice systems to raise awareness and skills in the innovation process, especially through co-creation across organizational boundaries.
Number: 4
Keywords: Co-création; Collaboration; Criminologie; Innovation sociale; Justice; Réservé UdeM; Santé

Nouvel outil pour mesurer les impacts de l’action collaborative - Fonds de recherche du Québec - FRQ - Fonds de recherche du Québec (2022)
Pour dresser le bilan de ses pratiques en début de pandémie, Moisson Montréal a utilisé un nouvel outil d’appréciation des effets de l’action intersectorielle locale, développé par des membres de la Chaire de recherche du Canada Approches communautaires et inégalités de santé. Cet outil interactif offert gratuitement en ligne aide des organismes tels que Moisson Montréal, qui œuvrent en réseau avec de multiples partenaires intersectoriels, à comprendre, modéliser et piloter les actions (tenue d’une activité, production d’un document, représentation, etc.) à entreprendre pour répondre à un besoin social, et à en analyser les retombées.
Keywords: Action collaborative; Collaboration; Communautaire; Inégalités; Libre accès; Outils; Québec; Réseau; Santé; Université

Identifying Topics and Difficulties on Collaboration in Social Innovation Environments - Pinheiro, Mariana; Chueri, Luciana; Santos, Rodrigo (XVI Brazilian Symposium on Information Systems, 2020)
There are currently several social innovation initiatives being developed in isolation, where each one has its own path. In this context, actors want to collaborate and be coordinated in a network in order to increase the development and dissemination of social innovations. The use of collaboration mechanisms gives rise to the expectation that actors playing in groups tend to achieve quantitative and qualitative performance higher than individual performances. While the potential benefits of collaboration are recognized, effectively achieving collaboration is still a challenge for social innovation. In this context, the objective of this study is to identify how the concepts of collaboration are recognized in social innovation environments. In addition, we investigated which mechanisms are used and what are the difficulties faced by actors in this context. To do so, a survey research on the aspects of collaboration in social innovation environments was conducted. Results shown that engagement is the most cited challenge related to human factors; from 30 techniques mentioned, Design Thinking is the most applied; and from 41 tools, Google Drive is the most cited. Results from qualitative analysis shown that collaboration is considered essential to social innovation environments, although there are several challenges reported.
Keywords: Amérique latine; Collaboration; Innovation sociale; Réservé UdeM

Analyse des processus de collaboration et de partage des connaissances dans une communauté de pratique engageant partenaires communautaires et universitaires - Valéry Psyché, Emmanuel Duplàa et Diane-Gabrielle Tremblay (2010)
Une communauté de pratique devrait être issue d’une initiative volontaire à l’intérieur d’une organisation, dont certains membres partagent des connaissances ou des savoirfaire qu’ils désirent améliorer. Le côté volontaire de l’initiative nécessite souvent une impulsion de démarrage, et une stratégie de dynamisation étalée dans le temps. Ceci représente tout un défi dans le cadre d’un réseau de recherche en partenariat qui regroupe des membres ayant un intérêt commun certes, mais répartis dans plusieurs pays et rattachés à divers organismes indépendants du réseau de recherche en partenariat où ils effectuent des travaux variés. 4 Notre objectif de recherche était donc : (1) de faire émerger une Communauté de pratique (CoP) au sein d’un programme de recherche en partenariat, notamment en lui offrant des outils propres au web social (site, blogue, infolettre, fil RSS, etc.) pour favoriser la collaboration de ses membres ; puis (2) d’observer l’évolution de cette CoP ; (3) et de dégager des techniques d’animation et de veille pour la mise en place de ce type de communauté de recherche. Dans ce texte, nous proposons un premier bilan, après un an, sur la pratique du partenariat et les actions menées afin de faire émerger une réelle communauté de pratique dans le cadre d’un programme de recherche en partenariat. Ceci constitue un défi important pour nombre de projets en partenariat, puisque plusieurs d’entre eux ont comme objectif non seulement de réaliser des recherches, mais de les réaliser en collaboration, et donc de soutenir les échanges entre les divers milieux (universitaire, communautaire, ou autre, selon les cas).
Issue: Note de recherche no 2010-08
Keywords: Collaboration; Communautaire; Libre accès; Partenariat; Université

Nouvel outil pour mesurer les impacts de l’action collaborative - Fonds de recherche du Québec - FRQ - Fonds de recherche du Québec (2022)
Pour dresser le bilan de ses pratiques en début de pandémie, Moisson Montréal a utilisé un nouvel outil d’appréciation des effets de l’action intersectorielle locale, développé par des membres de la Chaire de recherche du Canada Approches communautaires et inégalités de santé. Cet outil interactif offert gratuitement en ligne aide des organismes tels que Moisson Montréal, qui œuvrent en réseau avec de multiples partenaires intersectoriels, à comprendre, modéliser et piloter les actions (tenue d’une activité, production d’un document, représentation, etc.) à entreprendre pour répondre à un besoin social, et à en analyser les retombées.
Keywords: Action collaborative; Collaboration; Communautaire; Inégalités; Libre accès; Outils; Publication UdeM; Québec; Réseau; Santé; Université

Analyse des processus de collaboration et de partage des connaissances dans une communauté de pratique engageant partenaires communautaires et universitaires - Valéry Psyché, Emmanuel Duplàa et Diane-Gabrielle Tremblay (2010)
Une communauté de pratique devrait être issue d’une initiative volontaire à l’intérieur d’une organisation, dont certains membres partagent des connaissances ou des savoirfaire qu’ils désirent améliorer. Le côté volontaire de l’initiative nécessite souvent une impulsion de démarrage, et une stratégie de dynamisation étalée dans le temps. Ceci représente tout un défi dans le cadre d’un réseau de recherche en partenariat qui regroupe des membres ayant un intérêt commun certes, mais répartis dans plusieurs pays et rattachés à divers organismes indépendants du réseau de recherche en partenariat où ils effectuent des travaux variés. 4 Notre objectif de recherche était donc : (1) de faire émerger une Communauté de pratique (CoP) au sein d’un programme de recherche en partenariat, notamment en lui offrant des outils propres au web social (site, blogue, infolettre, fil RSS, etc.) pour favoriser la collaboration de ses membres ; puis (2) d’observer l’évolution de cette CoP ; (3) et de dégager des techniques d’animation et de veille pour la mise en place de ce type de communauté de recherche. Dans ce texte, nous proposons un premier bilan, après un an, sur la pratique du partenariat et les actions menées afin de faire émerger une réelle communauté de pratique dans le cadre d’un programme de recherche en partenariat. Ceci constitue un défi important pour nombre de projets en partenariat, puisque plusieurs d’entre eux ont comme objectif non seulement de réaliser des recherches, mais de les réaliser en collaboration, et donc de soutenir les échanges entre les divers milieux (universitaire, communautaire, ou autre, selon les cas).
Keywords: Collaboration; Communautaire; Idéation; dialogue et maillage; Libre accès; Partenariat; Université

Identifying Topics and Difficulties on Collaboration in Social Innovation Environments - Pinheiro, Mariana; Chueri, Luciana; Santos, Rodrigo (XVI Brazilian Symposium on Information Systems, 2020)
There are currently several social innovation initiatives being developed in isolation, where each one has its own path. In this context, actors want to collaborate and be coordinated in a network in order to increase the development and dissemination of social innovations. The use of collaboration mechanisms gives rise to the expectation that actors playing in groups tend to achieve quantitative and qualitative performance higher than individual performances. While the potential benefits of collaboration are recognized, effectively achieving collaboration is still a challenge for social innovation. In this context, the objective of this study is to identify how the concepts of collaboration are recognized in social innovation environments. In addition, we investigated which mechanisms are used and what are the difficulties faced by actors in this context. To do so, a survey research on the aspects of collaboration in social innovation environments was conducted. Results shown that engagement is the most cited challenge related to human factors; from 30 techniques mentioned, Design Thinking is the most applied; and from 41 tools, Google Drive is the most cited. Results from qualitative analysis shown that collaboration is considered essential to social innovation environments, although there are several challenges reported.
Keywords: Amérique latine; Collaboration; Innovation sociale; Réservé UdeM

Data activism and social change - Gutiérrez, Miren (Palgrave Macmillan, 2018)
This book efficiently contributes to our understanding of the interplay between data, technology and communicative practice on the one hand, and democratic participation on the other. It addresses the emergence of proactive data activism, a new sociotechnical phenomenon in the field of action that arises as a reaction to massive datafication, and makes affirmative use of data for advocacy and social change. By blending empirical observation and in-depth qualitative interviews, Gutiérrez brings to the fore a debate about the social uses of the data infrastructure and examines precisely how people employ it, in combination with other technologies, to collaborate and act for social change.
Keywords: Changement social; Collaboration; Data collaboratives; Réservé UdeM; Technologie

Le living lab, un intermédiaire d’innovation ouverte pour les territoires ruraux ou péri-urbains ? - Fasshauer, Ingrid; Zadra-Veil, Cathy (Innovations, 2020)
L’objectif de cet article est d’analyser une nouvelle forme organisationnelle, le living lab (LL) et sa capacité à favoriser l’innovation territoriale en milieu rural ou péri-urbain. A travers une revue de littérature et la mobilisation de la sociologie de l’acteur-réseau (Callon, 1986 ; Latour, 1987), nous positionnons les living labs comme intermédiaires d’innovation ouverte dont les caractéristiques permettent d’intégrer de nombreux acteurs hétérogènes, établissements publics, entreprises privées, associations et citoyens, sur des projets d’innovation. L’étude d’un LL rural met en évidence la capacité d’une telle structure à reconfigurer des réseaux d’acteurs pour proposer une série de tiers-lieux adaptés aux spécificités des territoires sur lesquels ils s’implantent. Cette recherche permet d’enrichir la réflexion la pérennisation des tiers-lieux ruraux et leurs spécificités par rapport aux espaces urbains.
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: De Boeck Supérieur
Keywords: Collaboration; Innovation; Innovation ouverte; Laboratoire vivant; Living Labs; Réservé UdeM; Économie collaborative

Les enjeux de la transition numérique et de l’innovation collaborative dans les mutations du travail et du management dans le secteur public - Zacklad, Manuel (Travailler dans les services publics : la nouvelle donne, 2020)
La transformation numérique et l’innovation collaborative ou les notions associées « d’intelligence collective », de « design thinking », « d’agilité » sont en passe de devenir les principaux concepts à la mode du management dans les organisations privées et publiques, au moins au sein des sièges et des directions centrales. Partant d’une description des spécificités des bouleversements introduits par la transition numérique et des technologies capacitantes qu’elle promeut, nous montrons comment les opérateurs sont parfois en demande de plus d’innovations numériques pour améliorer leurs conditions de travail et les services rendus au public, pour autant que celles-ci ne soient pas substitutives et excessivement rationalisantes. Les démarches d’innovation collaborative, soutenues par le haut management de manière parfois paradoxale, contribuent à faciliter ces mutations.
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0 Pages: 119-127 Publication Title: Travailler dans les services publics : la nouvelle donne
Keywords: Co-design; Collaboration; Innovation agile; Innovation collaborative; Intelligence collective; Numérique; Réservé UdeM; Secteur public

Contexts of Co-creation: Designing with System Stakeholders - Jones, Peter (Systemic Design: Theory, Methods, and Practice, 2018)
The concept of co-creation includes a wide range of participatory practices for design and decision making with stakeholders and users. Generally co-creation refers to a style of design or business practice characterized by facilitated participation in orchestrated multi-stakeholder engagements, such as structured workshops and self-organizing modes of engagement. Co-creation envelopes a wide range of skilled social practices that can considerably inform and enhance the effectiveness of organizational development, collaboration, and positive group outcomes. New modes of co-creation have emerged, evolving from legacy forms of engagement such as participatory design and charrettes and newer forms such as collaboratories, generative design, sprints, and labs. Often sessions are structured by methods that recommend common steps or stages, as in design thinking workshops, and some are explicitly undirected and open. While practices abound, we find almost no research theorizing the effectiveness of these models compared to conventional structures of facilitation. As co-creation approaches have become central to systemic design, service design, and participatory design practices, a practice theory from which models might be selected and modified would offer value to practitioners and the literature. The framework that follows was evolved from and assessed by a practice theory of dialogic design. It is intended to guide the development of principles-based guidelines for co-creation practice, which might methodologically bridge the wide epistemological variances that remain unacknowledged in stakeholder co-creation practice.
P. Jones est professeur agrégé à l'Université OCAD Toronto. Il enseigne dans les programmes d'études supérieures : prospective stratégique et innovation, et en conception pour la santé. Recherche sociale et design, conception de services | systèmes pour la santé, conception de systèmes sociaux. Ouvrage qui propose des explications entourant le concept de co-création par l’usage de pratique de conception participatives - « pour la conception et la prise de décision avec les parties prenantes et les utilisateurs ». Explication des nouveaux modes de co-création qui ont émergé.
Keywords: Co-création; Collaboration; Idéation; dialogue et maillage; Japon; Réservé UdeM

University Medialabs: New Learning Spaces for Educational Innovation - Almaraz-Menéndez, Fernando; Martín-García, Teresa; López-Esteban, Carmen (Journal of Strategic Innovation and Sustainability, 2021)
Higher Education Institutions, like many other organizations, are facing pressure from the development of digital technologies as a push towards the digitization of their activities and towards a type of change that some describe as disruptive and that forces them to review their processes and structures. This article describes the case of the medialab of the University of Salamanca, MEDIALAB USAL, as an experience of new learning space in higher education. Its origin is explained from the experiences of citizen technology laboratories and experimental laboratories at the point of intersection between Art, Science and Technology. Its structure and working methods are explained, and its activities are illustrated through the description of four educational innovation projects based on different digital technologies: a mathematics didactics project using AppInventor, Wikipedia as a tool for knowledge generation, Arduino for innovation in the teaching of Fine Arts and a university Hackathon as an activity to introduce students to social and entrepreneurial innovation processes.
Number: 4
Keywords: Collaboration; Durabilité; Europe; Hackathon; Innovation pédagogique; Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Médialab; Technologies; numérique

Using Social Innovation as a Theoretical Framework to Guide Future Thinking on Facilitating Collaboration Between Mental Health and Criminal Justice Services - Hean, Sarah; Willumsen, Elisabeth; Ødegård, Atle; Bjørkly, Stål (International Journal of Forensic Mental Health, 2015)
Offender mental health is a major societal challenge. Improved collaboration between mental health and criminal justice services is required to address this challenge. This article explores social innovation as a conceptual framework with which to view these collaborations and develop theoretically informed strategies to optimize interorganizational working. Two key innovation frameworks are applied to the offender mental health field and practice illustrations provided of where new innovations in collaboration, and specifically co-creation between the mental health system and criminal justice system, take place. The article recommends the development of a competency framework for leaders and front line staff in the mental health system and criminal justice systems to raise awareness and skills in the innovation process, especially through co-creation across organizational boundaries.
Keywords: Co-création; Collaboration; Criminologie; Innovation sociale; Justice; Réservé UdeM; Santé